Repurposing and Renovating Space for High-Density Storage: Kansas State University Libraries' Answer to Additional Collections Space. Issue 2 (3rd April 2017) - Turvey-Welch, Michelle R.; Johnson, Roberta L.
ABSTRACT: While many libraries have built new high-density storage facilities, fewer academic libraries have repurposed and renovated an existing building for that new end. This article details Kansas State University Libraries' experience renovating an existing structure for high-density storage purposes and the improved collection management options that resulted.